STUDI TENTANG EKSPLOITASI BATU KARANG DI SEPANJANG PESISIR PANTAI MAILEPPET KECAMATAN SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - Kancius, Petrus; Rianto, Slamet; Yuherman, Yuherman (Pendidikan Geografi, 2013)
Waters Maileppet village is one of the areas that have extensive coral ecosystems. Result of taking rock massive damage and death rock in the waters Maileppet village, so it is bad for the ecosystem of the sea , and other biota that are in the waters of the village Maileppet This study aims to obtain data, information and an overview of the exploitation of coral reefs along the coast of Maileppet village South Siberut district Mentawai Islands regency views of : 1 ) knowledge of the community, 2 ) the attitude of the community, 3 ) the level of income, and 4 ) level of education .This research is a descriptive study that aims to show the state as it is appropriate to show that based on the calculation of the average percentages and other statistics . Population in this research is all the people who exploit the rocks along the coast of Maileppet village South Siberut district Mentawai Islands regency, amounting to 60 families. The study sample was taken with the sampling method of total population sampled throughout the study so that the study sample was 60 families.The research found that : 1) Public awareness of the exploitation of coral reefs along the coast of Maileppet village South Siberut district Mentawai Islands regency included both with the percentage of 79,85%, 2) public attitudes about the exploitation of coral reefs along the coast of Maileppet village South Siberut district Mentawai Islands regency included both with the percentage of 85,24%, 3) level of income of the people in the villages along the coastal of Maileppet village South Siberut district Mentawai Islands regency is generally > Rp 1000.000 - 2000.000/ month (65,0%) and including high and 4 ) public education level last Maileppet village South Siberut district Mentawai Islands regency is generally complete primary school ( 65,00 %) and never get a non-formal education (6333%)